# math

posted by .

Perform the indicated operation(s) and express the result in standard form. Leave answers in terms of square roots (do not use decimals).
(-9-sqrt-3)^2

• math -

(-9 - sqrt(-3))^2 =
(-9 - sqrt(3*-1)^2=
(-9 - isqrt(3))^2 =
81 + 18isqrt3 + 3 =
3(27 + 6isqrt3 + 1).

## Similar Questions

2. ### math

solve 2x^2+3x+8=0 and express the solutions in a+bi form. Let's use the quadratic formula to solve for x and express those solutions in a+bi form. x = [-b + or - sqrt(b^2 - 4ac)]/2a Note: sqrt = square root. a = 2, b = 3, and c = 8 …
3. ### math,algebra,help

Directions are simplify by combining like terms. x radiacal 18 -3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which reduces …
4. ### Math

How do you find a square root of a number that's not a perfect square?

I some problems that I need help with please. Add or subtact as indicated and write the results in standard form. 4. 6-(-5+7i)-(7-2i) Divide and express the result in standard form. --These problems I don't understand, do you have …
6. ### Precalculus

Perform the indicated operation and the write the result in standard form (6+ sq root -5)(6 + sq root -7)=